Colonial Korea’s Perspectives and Literary Representations of the First World War: A Focus on the 1910s Maeil-Sinbo and Shinhan-Minbo (New Korea) - Ryuem, Chang-Dong (International Journal of Korean Humanities and Social Sciences, 2025)
This paper examines the reception and narrative appropriation of First World War in colonial Korea by analyzing serialized literary texts from two contemporaneous newspapers: the Maeil Sinbo and Shinhan Minbo (The New Korea). By comparing works such as Guju Yeolgukji in the Maeil Sinbo and The Biggest Theatre in the World and Iron-Blooded Lovebirds in The New Korea, the study reveals contrasting perspectives shaped by differing political and media environments. Serialized from 1914, Guju Yeolgukji initially conveyed the First World War through an entertainment-oriented lens, focusing on the ethnic tensions between Germanic and Slavic peoples. However, by 1915, its narrative shifted to the Battle of Qingdao, redirecting attention toward celebrating Japan’s military achievements. The text makes no mention of any connection between the war and colonial Korea. In contrast, The Biggest Theatre in the World interprets the outbreak of the war as stemming from German ambition and Austrian vengeance, while highlighting the French people’s will to resist aggression – thus offering a critical portrayal of the invading powers. Yet the work simultaneously laments the absence of direct involvement by colonial Koreans, ultimately framing the war as a conflict among white European powers – a ‘foreign war.’ The subsequent serial Iron-Blooded Lovebirds, published between 1916 and 1917, returns to the Balkan Wars, one of the antecedents of First World War, and emphasizes the national spirit of the Serbian people. This shift reflects an emerging perspective that viewed the global war as an opportunity for the liberation of oppressed nations. This trajectory culminates in the subsequent work Dongpo, which envisions a future war for Korean independence, thereby extending the narrative toward an imagined postwar world order. The voice of hope and passion for the coming postwar world is vividly expressed in the poem World Democracy written by a Korean student who had participated in the war. After the end of First World War, the postwar world was imbued with a spirit of revolution. Korea’s March First Movement was situated within this global revolutionary current, and Shinhan Minbo referred to it as the ‘Korean Revolution’, aligning it with contemporaneous uprisings around the world. These past revolutions did not remain mere historical events; rather, they functioned as living memories that offered Korean independence activists new possibilities for political imagination and revolutionary praxis.